Electrokinetic Study of Gallium(III) with DL α-Alanine in Aqueous and 25% Ethanol in Water (v/v) at D.M.E. - Sharma, Vinita; Gupta, K.D. (Asian Journal of Chemistry, 2016)
The polarographic behaviour of gallium(III) in DL α-alanine in aqueous and 25% ethanol-water (v/v) media has been studied. The reduction of Ga(III) (1 mM) has been found to be irreversible and diffusion controlled in the presence of 0.1 M KCl and 0.0002% triton-X-100. The values of kinetic parameters, transfer coefficient (αn) and formal rate constant (k0f,h) of the electrode reactions have been calculated by Koutecky’s method. The values of thermodynamic parameters, the free energy of activation (ΔG≠), the enthalpy of activation (ΔH≠) and the entropy of activation (ΔS≠) have also been determined at 30°C.